Small Social Incentives Did Not Improve the Survey Response Rate of Patients Who Underwent Orthopaedic Surgery: A Randomized Trial. Issue 7 (July 2019) - Warwick, Hunter; Hutyra, Carolyn; Politzer, Cary; Francis, Andrew; Risoli, Thomas; Green, Cynthia; Verma, Nikhil; Huettel, Scott; Mather, Richard C.
Abstract: Background: The generalizability of data derived from patient-reported outcome measures (PROMs) depends largely on the proportion of the relevant population that completes PROM surveys. However, PROM survey responses remain low, despite efforts to increase participation. Social incentives, such as the offer to make a charitable donation on behalf of the survey respondent, have generally not been effective where online surveys are concerned, but this has not been extensively tested in medicine. Questions/purposes: (1) Do personalized social incentives increase response rates or response completeness for postoperative PROM surveys in an orthopaedic population? (2) Are there demographic factors associated with response and nonresponse to postoperative PROM surveys? (3) Are some demographic factors associated with increased response to social incentive offers? Methods: Participants were selected from an institutional orthopaedics database. Patients were older than 18 years, had an email address on file, and had undergone one of the following procedures 1 to 2 years ago: Achilles tendon repair, ACL reconstruction, meniscectomy, hip arthroscopy, TKA, or THA. Of 4685 eligible patients, 3000 (64%) were randomly selected for inclusion in the study. Participants were randomized to one of four groups: (1) control: no incentive (n = 750); (2) patient donation: offer of a USD 5 donation to provide medical supplies to a pediatric orthopaedic patient (n = 751); (3) research donation: offer of a USD 5 donation to a procedure-specific research program (n = 749); or (4) explanation: explanation that response supports quality improvement (n = 750). The four groups did not differ regarding patient age, gender, race, procedure type, or time since procedure. All patients were sent an email invitation with the same PROM survey link. The proportion of patients who responded (defined here as the response rate) was measured at 4 weeks and compared between intervention groups. We used a logistic regression analysis to identify demographic factors associated with response while controlling for confounding variables and performed subgroup analyses to determine any demographic factors associated with increased response to social incentives. Results: There was no difference in the overall response rate (research donation: 49% [353 of 725], patient donation: 45% [333 of 734], control: 45% [322 of 723], explanation: 44% [314 of 719]; p = 0.239) or response completeness (research donation: 89% [315 of 353], patient donation: 90% [301 of 333], control: 89% [287 of 322], explanation: 87% [274 of 314]; p = 0.647) between the four groups. Women (odds ratio [OR], 1.175; p = 0.042), older patients (< 58 years: OR, 1.016 per 1-year increase; p = 0.001; 58-64 years: OR, 1.023 per 1-year increase; p < 0.001; > 64 years: OR, 1.021 per 1-year increase; p < 0.001), and white patients (OR 2.034 compared with black patients, p < 0.001) were slightly more likely to respond, after controlling for potential confounding variables such as gender, age, race, and procedure type. In subgroup analyses, men (research donation: 49% [155 of 316], patient donation: 45% [146 of 328], control: 40% [130 of 325], explanation: 39% [127 of 325]; p = 0.041) and patients younger than 58 years (research donation: 40% [140 of 351], control: 35% [130 of 371], patient donation: 32% [113 of 357], explanation: 27% [93 of 340]; p = 0.004) were slightly more likely to respond to the research donation than those with other interventions were. Conclusions: Despite small effects in specific subgroups, personalized social incentives did not increase the overall response to postoperative orthopaedic surveys. Novel and targeted strategies will be necessary to reach response thresholds that enable healthcare stakeholders to use PROMs effectively. Level of Evidence: Level I, therapeutic study.